The role of international organisations and non-governmental organisations in information support for agricultural policy formulation in Kenya - Owino, F. (Technical Centre for Agricultural and Rural Cooperation, 1999)
Like most countries in sub-Saharan Africa, Kenya needs to improve its capacity to generate agricultural information for use by policy-makers...